RELEVANSI DAN KEBERLANJUTAN PEMBELAJARAN SASTRA INDONESIA DI ERA DIGITAL - Sudarsih, Lilis (Universitas Islam Zainul Hasan Genggong, 2024)
Advances in digital technology have significantly changed the educational landscape, including the teaching and learning of literature. This research explores the relevance and sustainability of learning Indonesian literature in a digital environment. It examines the dynamics, challenges and opportunities that arise from digital platforms in the context of Indonesian literature education. It explores how digital tools and resources are reshaping pedagogical approaches, curriculum development, and student engagement in the study of Indonesian literature. Using a qualitative methodology it investigates the perceptions of educators, students and stakeholders regarding the integration of digital technologies in literature learning. It examines the effectiveness of digital platforms in increasing access to Indonesian literary works, encouraging critical thinking skills, and promoting cultural appreciation and identity. It also assesses the sustainability of digital initiatives in literature education, taking into account factors such as infrastructure, digital literacy and institutional support. The findings of this study contribute to the discourse on the role of digital technology in maintaining the relevance and vibrancy of learning Indonesian literature. Ultimately, this research advocates for a balanced approach that integrates traditional pedagogical principles with innovative digital practices to enrich the learning experience and preserve appreciation for Indonesia's literary heritage.